1998
DOI: 10.1128/mcb.18.6.3112
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Vascular Endothelial Growth Factor mRNA by Internal Ribosome Entry: Implications for Translation under Hypoxia

Abstract: Vascular endothelial growth factor (VEGF) is a hypoxia-inducible angiogenic growth factor that promotes compensatory angiogenesis in circumstances of oxygen shortage. The requirement for translational regulation of VEGF is imposed by the cumbersome structure of the 5 untranslated region (5UTR), which is incompatible with efficient translation by ribosomal scanning, and by the physiologic requirement for maximal VEGF production under conditions of hypoxia, where overall protein synthesis is compromised. Using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
359
1
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 465 publications
(378 citation statements)
references
References 38 publications
(40 reference statements)
13
359
1
5
Order By: Relevance
“…In addition, while the viral IRES is about 450 bp in length, mammalian IRESes range in size from under 100 bp 14 to approximately 1 kb. 11 For example, the smaller mammalian IRESes from the GTX (glial and testis-specific homeobox protein) or BIP genes may be useful for incorporation into vectors with limited packaging capacity, such as those derived from AAV (adeno-associated virus) or SV40 (simian virus 40).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, while the viral IRES is about 450 bp in length, mammalian IRESes range in size from under 100 bp 14 to approximately 1 kb. 11 For example, the smaller mammalian IRESes from the GTX (glial and testis-specific homeobox protein) or BIP genes may be useful for incorporation into vectors with limited packaging capacity, such as those derived from AAV (adeno-associated virus) or SV40 (simian virus 40).…”
Section: Discussionmentioning
confidence: 99%
“…12 However, it has been reported that a truncated version of the mouse Vegf IRES containing the 5' end of the Vegf 5'UTR and a portion of IRES A is better than a full-length 1 kb fragment containing both IRES A and IRES B, in mediating downstream gene expression. 11 We therefore compared the performances of the human full-length (VEGF IRES) and truncated (V163 IRES) versions against the EMCV IRES in KB-3-1 cells. The results show the V163 IRES to be capable of mediating significantly better downstream gene expression than either the complete VEGF IRES (P Ͻ 0.05) or EMCV IRES (P Ͻ 0.05) (Figure 4).…”
Section: Full-length But Not Truncated Vegf Ires Mediates Higher Expmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is mediated by structured regions of RNA termed internal ribosome entry segments (IRES), and these have the ability to direct ribosome binding some considerable distance (up to 1000 nts) from the 5' end of the message. IRESs were originally discovered in picornaviral mRNAs, but have now been identi®ed in a number of eukaryotic mRNAs, the protein products of which are involved in the control of cell growth including, FGF-2 (Vagner et al, 1995), VEGF (Miller et al, 1998;Stein et al, 1998), PDGF (Bernstein et al, 1997) and c-myc (Nanbru et al, 1997;Stoneley et al, 1998) and cell death Holcik et al, 1999). In the case of c-myc we have shown that initiation of protein synthesis can occur by two distinct mechanisms; cap-dependent scanning and IRES mediated .…”
mentioning
confidence: 98%